Kajian Filosofis Tentang Keadilan Sosial Dari Pemikiran Plato - Dules Ery Pratama Hrp; Yakobus Ndona (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Philosophical study of social justice from Plato's thought Throughout the history of philosophy, the topic of justice has been a very important topic. Theoretical thinkers such as utilitarianism, intuitionism, eudaimonism, perfectionism, liberalism, communitarianism, and socialism have discussed this topic. The core of political research from the time of Plato to the present is justice. Questions of fairness cannot be determined by the standards used to determine whether something is fair. Different versions of answers regarding the meaning of justice are often considered unsatisfactory, so they cannot be separated from the debate which ultimately constructs the meaning of justice itself, even into a relative formulation. This problem ultimately encouraged many groups to take an alternative path by returning the meaning of justice to those who set the laws and regulations and to judges who will develop their own considerations. This article will discuss the concept of justice from the perspective of Pre-Christian philosophers, especially Plato. Philosophically, there are two ways of expressing justice: First, the view that justice means harmony between the implementation of rights and the implementation of obligations according to the